Pembelajaran Mendalam (Deep Learning) dalam Kurikulum Merdeka: Pemetaan Tren Penelitian Melalui Analisis Bibliometrik - Thufail Mujaddid Al-Qoyyim; Siti Maulidiya Nabila (Pascasarjana Universitas Qomaruddin, 2025)
This study aims to analyze research trends on deep learning pedagogy within the context of Indonesia’s Merdeka Curriculum during the period 2016–2025. The research employed a bibliometric analysis using the Dimensions database, with searches conducted through keywords such as “pembelajaran mendalam,” “meaningful learning,” and “Merdeka Curriculum.” Metadata including titles, publication years, authors, keywords, and citations were extracted and analyzed using VOSviewer. The analysis consisted of four stages: descriptive trend mapping, network visualization, overlay visualization, and density visualization. The findings reveal a significant increase in publications, with a sharp surge in 2025 following the release of official regulations that explicitly positioned deep learning as the core pedagogical approach of the Merdeka Curriculum. The network visualization highlights dominant foci on approach, practice, development, and project, while the overlay visualization shows a shift from descriptive documentation of learning processes toward evaluation and strategy development. Density visualization further identifies emerging research opportunities in technology integration, character building, and institutional support. Practical implications suggest that teachers should simplify essential content, employ formative assessment, and design contextual projects, while schools are encouraged to provide professional training, collaborative spaces, and flexible policies. Overall, the study confirms that deep learning pedagogy is not only academically relevant but also strategically vital in strengthening student competencies and the Profil Pelajar Pancasila.